PENGEMBANGAN MULTIMEDIA INTERAKTIF DESCRIPTIVE TEXT PADA MATA PELAJARAN BAHASA INGGRIS DI KELAS VII SMP - Erlangga Oktavio, Duta; Novrianti; Ade Kurnia Yusri, Meldi; Pratiwi, Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an interactive multimedia for teaching descriptive text to seventh-grade junior high school students that is valid, practical, and suitable for use as an alternative learning medium. The study was motivated by observations and interviews conducted at SMP Negeri 34 Padang, which revealed that descriptive text instruction mainly relied on textbooks and lecture-based methods without the support of interactive learning media. As a result, students experienced difficulties in understanding text structure and vocabulary and showed low learning motivation. This research employed the Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The multimedia was developed using Articulate Storyline by integrating text, images, audio, animations, videos, and interactive exercises. Data were collected through validation sheets completed by material and media experts, as well as practicality questionnaires administered to teachers and students. The data were analyzed using descriptive quantitative techniques with a Likert scale. The results indicated that the developed multimedia was highly valid, with material and media validity scores of 90% and 98.18%, respectively. The practicality test yielded a score of 93.60%, categorized as highly practical. Therefore, the interactive multimedia is considered appropriate as an engaging, interactive, and effective learning medium to improve students' understanding of descriptive texts in seventh-grade English classes.